Investigating the Islamic Architecture By Focusing on the City of Yazd, Iran - Mohammad A. Mulazadeh (MAQOLAT: Journal of Islamic Studies, 2024)
This research aimed to investigate Islamic architecture and its architectural impact on the city form and building structure in the Islamic world. This research's theoretical base was founded on the frequently used term 'Islamic architecture' in the literature that allegedly has created its physical expression. The method of literature review was used to confirm whether 'Islamic architecture'  created its iconic physical structures. The Iranian city of Yazd was selected as a case study to document if any identified element in the ancient city of Yazd was affected by the so called 'Islamic architecture'. The reviewed literature revealed no agreement among researchers to confirm that there is a recognised physical form, theory, or method to represent 'Islamic architecture' in the Islamic world. This finding and literature review point to a clear conclusion that there was no typical form of architectural design that could show the existence of so-called 'Islamic architecture' all over the Islamic world. This paper may stimulate and excite the Islamic advocates’ interest to further investigate and introduce evidence of recognised physical form or iconic structure to portray Islamic architecture.